Microorganisms isolated from thermoplastic masks and storage racks in head and neck cancer patients with radiation dermatitis - Özlem Koca; Timur Koca; Rahmi Atil Aksoy; Aylin Fidan Korcum (Scientific Reports, 2024)
Abstract Healthcare-associated infections (HAIs) remain a critical public health issue, as they contribute to prolonged treatment duration, increased healthcare costs, and heightened risks of morbidity and mortality. In head and neck cancer patients undergoing radiotherapy, thermoplastic masks (TMs), which come into direct contact with the skin, represent a potential vector for infection. Additionally, the storage racks where these masks are kept may also facilitate microorganism transmission. Our study aimed to isolate and identify microorganisms from infective skin lesions secondary to radiation dermatitis in head and neck cancer patients, as well as from the TMs and storage racks, and to evaluate the antibiotic resistance profiles of the isolated microorganisms. The study included 71 locally advanced head and neck cancer patients who underwent radiotherapy between August 2022 and November 2023. Patients were monitored daily, and their skin evaluations were made according to Common Terminology Criteria for Adverse Events (CTCAE) version 4.0. Grade 2 and 3 radiodermatitis was observed in 29 of these 71 patients. Samples were collected using sterile swabs from the skin lesions on the head and neck area, the inner surfaces of the TM, and the storage rack from 29 patients. Samples were inoculated into enrichment and selective media. After the growing microorganisms were identified, antimicrobial susceptibility was evaluated using conventional methods and automated systems according to the European Committee on Antimicrobial Susceptibility Testing (EUCAST) criteria. At least one type of microorganism was isolated from the skin samples of infected patients, and double growth was detected in two patients. Among the samples, 2 were methicillin-resistant coagulase-negative Staphylococcus (MRCNS), 1 was methicillin-resistant Staphylococcus aureus (MRSA), 1 was Candida albicans (C. albicans), 15 were methicillin-sensitive coagulase-negative Staphylococcus (MSCNS), 1 was methicillin-sensitive Staphylococcus aureus (MSSA), 1 was Bacillus subspecies (Bacillus spp.) and 3 were Corynebacterium diphtheriae (C. diphtheriae). Coagulase-negative Staphylococcus strains were isolated from the skin of 14 of 19 patients with grade 2 radiation dermatitis, whereas CNS strains were isolated from only 2 of 10 patients with grade 3 radiation dermatitis. Among the gram-negative bacteria, 3 Pseudomonas aeruginosa (P. aeruginosa), 2 Enterobacter cloacae (E. cloacae), 1 Klebsiella pneumoniae (K. pneumoniae) and 1 Moraxella catarrhalis (M. catarrhalis) strain were isolated. Sixteen (55.1%) of the TMs used in 29 patients and 20 (68.9%) of the storage racks harbored microorganisms, including HAI agents and flora bacteria. Bacteria colonize TMs and storage racks where they are risk factors for secondary skin infections in radiation dermatitis lesions that develop on the skin of head and neck cancer patients. Decontamination procedures should be meticulously applied to surfaces such as TMs and their storage racks during the course of radiotherapy.